2019
DOI: 10.1080/21691401.2019.1600529
|View full text |Cite
|
Sign up to set email alerts
|

Using CuO nanoparticles and hyperthermia in radiotherapy of MCF-7 cell line: synergistic effect in cancer therapy

Abstract: The aim of this paper was examining the combined impacts of CuO nanoparticles (CuO NPs), hyperthermia (H), and irradiation (R) on an increment of MCF-7 cells. The MTT assay was employed to assess the antiproliferative effects of CuO NPs (25, 50, and 100 lg/ml), hyperthermia (41 C for 1 h), and irradiation (200 cGy). Moreover, the perniciousness was estimated through the survival capability of cells, and apoptosis, ROS production, and levels of caspase-3,-8 and-9 proteins were determined. A significant (p < .01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…It has been reported that HSP, which confers thermotolerance to cells, can also be expressed by mechanical stimulation rather than heat shock 25 . Alternatively, it was recently reported that combinations of hyperthermia and other stimuli enhanced the cell killing effect 10 , 15 , 26 , 27 . On the other hand, in previous studies, owing to the lack of a system that achieves immediate temperature regulation, there was a gap between the set temperature and the actual realized culture temperature to which cells were exposed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HSP, which confers thermotolerance to cells, can also be expressed by mechanical stimulation rather than heat shock 25 . Alternatively, it was recently reported that combinations of hyperthermia and other stimuli enhanced the cell killing effect 10 , 15 , 26 , 27 . On the other hand, in previous studies, owing to the lack of a system that achieves immediate temperature regulation, there was a gap between the set temperature and the actual realized culture temperature to which cells were exposed.…”
Section: Discussionmentioning
confidence: 99%
“…Absorption at 570 nm was measured by Elisa reader (BioTek Instrument, USA). The half maximal inhibitory concentration (IC50) was determined by linear regression based on Equation ( 4) [25]. In order to calculate the cell viability, Equation (5) was used as follows: [26]…”
Section: In Vitro Cytotoxicity Studiesmentioning
confidence: 99%
“…Breast cancer is the second driving reason for cancer-based mortality among women and the most generally identified cancer after skin-related cancers [3]. Radiation therapy, so called radiotherapy, is among the most important methods of cancer treatment, which applies ionizing radiation (IR) to eradicate cancerous cells [4]. The radiotherapy not only is considered as primary therapy, but also is used along with chemotherapy, hormone therapy, and surgery [5,6].…”
Section: Introductionmentioning
confidence: 99%